Perinatal factors and breast cancer risk among Hispanics - Maureen Sanderson; Adriana Pérez; Mirabel L. Weriwoh; Leah R. Alexander; Gerson Peltz; Vincent Agboto; Heather O'Hara; Waseem Khoder (Springer, 2019)
Purpose: This study assessed whether perinatal factors were associated with breast cancer among Hispanics, a group with fairly low incidence rates of breast cancer. Methods: Data were used from a case-control study of breast cancer among Hispanics aged 30-79 conducted between 2003 and 2008 on the Texas-Mexico border. In-person interviews were completed with 188 incident breast cancer cases ascertained through surgeons and oncologists, and 974 controls (with respective response rates of 97% and 78%). Results: Relative to birth weight 2500-3999 g, there was no elevation in breast cancer risk for birth weight of ⩾4000 g (odds ratio [OR] 0.76, 95% confidence interval [CI] 0.47-1.21). Conclusions: The results tended to differ slightly from previous studies of this topic perhaps owing to the different hormonal milieu among Hispanics relative to Caucasians, African Americans and Asians in whom all previous studies of this topic have been conducted. Confirmation of these findings in larger studies may assist in determining how hormonal mechanisms responsible for breast cancer differ by ethnicity.